Sixty Years After the First Description: Genome Sequence and Biological Characterization of European Wheat Striate Mosaic Virus Infecting Cereal Crops - Sõmera, Merike; Kvarnheden, Anders; Desbiez, Cécile; Blystad, Dag-Ragnar; Sooväli, Pille; Kundu, Jiban Kumar; Gantsovski, Mark; Nygren, Jim; Lecoq, Hervé; Verdin, Eric; Spetz, Carl; Tamisier, Lucie; et al. (Phytopathology, 2020)
High-throughput sequencing technologies were used to identify plant viruses in cereal samples surveyed from 2012 to 2017. Fifteen genome sequences of a tenuivirus infecting wheat, oats, and spelt in Estonia, Norway, and Sweden were identified and characterized by their distances to other tenuivirus sequences. Like most tenuiviruses, the genome of this tenuivirus contains four genomic segments. The isolates found from different countries shared at least 92% nucleotide sequence identity at the genome level. The planthopper Javesella pellucida was identified as a vector of the virus. Laboratory transmission tests using this vector indicated that wheat, oats, barley, rye, and triticale, but none of the tested pasture grass species (Alopecurus pratensis, Dactylis glomerata, Festuca rubra, Lolium multiflorum, Phleum pratense, and Poa pratensis), are susceptible. Taking into account the vector and host range data, the tenuivirus we have found most probably represents European wheat striate mosaic virus first identified about 60 years ago. Interestingly, whereas we were not able to infect any of the tested cereal species mechanically, Nicotiana benthamiana was infected via mechanical inoculation in laboratory conditions, displaying symptoms of yellow spots and vein clearing evolving into necrosis, eventually leading to plant death. Surprisingly, one of the virus genome segments (RNA2) encoding both a putative host systemic movement enhancer protein and a putative vector transmission factor was not detected in N. benthamiana after several passages even though systemic infection was observed, raising fundamental questions about the role of this segment in the systemic spread in several hosts.
Keywords: virology; oat striate and red disease; wheat striate mosaic; jedlá semena; Švédsko; cereal virus; virome; wheat virus; Javesella; Plant Viruses; rostlinné viry; Sweden; Plant Diseases; genom virový; zvířata; Norway; Hemiptera; European wheat striate mosaic virus; Edible Grain; Mosaic Viruses; insect vector transmission; tenuivirus; viry mozaiky; Genome, Viral; nemoci rostlin; Animals; Norsko